Assessing Temporal Changes in Groundwater Recharge Using Spatial Variations in Groundwater Ages. Issue 8 (31st July 2020) - McCallum, James L.; Dogramaci, Shawan; Bai, Albert; Cook, Peter G.; Engdahl, Nicholas B.; Simmons, Craig T.; Skrzypek, Grzegorz; Grierson, Pauline F.
Abstract: Determining variations in groundwater replenishment over a variety of time scales remains a challenge in the management and protection of groundwater resources. Specifically, capacity to use hydraulic data collected in small windows of time to infer long‐term changes can be limited by system responses. Groundwater ages offer an alternative approach as they represent the time since recharge occurred. Here we use spatial variations in groundwater ages and environmental tracer concentrations to infer temporal variations in groundwater recharge and apply the method to a mine site in northwest Australia, where a stream has been modified from ephemeral to perennial, resulting in enhanced recharge to groundwater. Measurements of 14 C and CFC‐12 at five transects along an ephemeral stream were interpreted with the new model to identify recharge rates and the proportion of recharge attributable to enhanced versus natural recharge from flood events. Enhanced recharge varied between 0.03 and 0.66 m/year compared to flood‐generated recharge values ranging between 0.07 and 1.3 m/year. Our results show that spatial variations of groundwater ages and environmental tracer concentrations preserve information about past flow regimes. While our study has demonstrated decadal variations in recharge, application of the method on larger scales could infer much greater extent of temporal variability in recharge, with the potential for significant insight into climate effects on groundwater. Plain Language Summary: Groundwater is a very important source of water supplying 40% of population globally. The process that replenishes groundwater is known as recharge and reflects climate, plants, and soil conditions, so changes in any of these factors will modify the groundwater recharge. Much of the water in aquifers is thousands of years old, so it is challenging to understand the conditions that led to this recharge using measurements taken today. Our study uses the variability of groundwater ages at different locations in an aquifer to determine how recharge has changed over time. We can also better understand these systems using environmental tracers, which are chemical compounds with distinct signals that change over time. The amount of groundwater replenishment can be determined by measuring the same compounds in groundwater, and having a model of how they move through the groundwater system. We investigated a system where a usually dry creek (ephemeral) had been made permanently wet (perennial). We were able to show that in areas of the stream close to where flow is added, the natural replenishment of groundwater was supplemented by additional infiltration of mine discharge water. This effect reduced along the creek further from the discharge point. Our approach can now be used to better predict how changing climate and land management may impact on sustainable use of groundwater. Key Points: We demonstrate that spatial variations in groundwater ages can be used to infer temporal changes in recharge We used measurements of 14 C and CFC‐12 to quantify changes in ephemeral recharge from a stream in northwest Australia We found that infiltration of mine discharge water increased recharge by up to 75% of natural recharge values